Effects of aegeline, a main alkaloid of aegle marmelos correa leaves, on the histamine release from mast cells. - Nugroho, Agung Endro; Riyanto, Sugeng; Md.Sukari, Mohd. Aspollah; Maeyama, Kazutaka (University of Karachi. Faculty of Pharmacy, 2011)
Aegeline or N-[2-hydroxy-2(4-methoxyphenyl) ethyl]-3-phenyl-2-propenamide is a main alkaloid isolated from Aegle marmelos Correa collected in Yogyakarta Indonesia. In our study, we investigated the effects of aegeline on the histamine release from mast cell. The study was performed by using (1) rat basophilic leukemia (RBL-2H3) cell line, and (2) rat peritoneal mast cells (RPMCs). DNP24-BSA, thap pe of mast cell and also involved some mechanisms related to intracellular Ca 2+ signaling events via the same target of the action of thapsigargin or downstream process of intracellular Ca 2+ signaling in mast cells.